JUDICIAL INVESTIGATORS OF STAVROPOL PROVINCE AND EVERYDAY PROFESSIONAL ACIVITY - Yu. P. Ponomareva (Гуманитарные и юридические исследования)
The article discloses peculiarities of professional activities of judicial investigators in Stavropol province as representatives of the judicial officials of the second half of XIX - early XX centuries on the basis of everyday life history approaches. The article analyzes professional quality and level of training of investigators, the impact of social and material conditions in the official daily life. For example, pre-revolutionary activities of investigators showing peculiarities of the legal system of Stavropol.